138k views
5 votes
Simplify the expression 2 × 36 − 24 ÷ 6

User Kissed
by
5.7k points

2 Answers

6 votes

Answer:

68

Explanation:

*Remember the order of operations PEMDAS*(Parentheses, Exponents, Multiplication and Division, Addition and Subtraction)

  1. 2 x 36 = 72
  2. 24 / 6= 4
  3. now, 72 - 4= 68

hope it helps:)

User Rafael Berro
by
6.6k points
3 votes

Answer:

68

Explanation:

P- parentheses

E- exponential

M- multiplication

D- division

A- addition

S- subtraction

2 x 36 = 72

72 - 24 ÷ 6

24 ÷ 6 = 4

72 - 4 = 68

User Yash Srivastava
by
6.2k points